Effects of trauma-related amputations in children on caregivers: An exploratory descriptive study in a developing country. - Patience Achiamaa Barnie; Veronica Millicent Dzomeku; Abigail Aban Tetteh; Bernard Asamoah Barnie; Charles Mock; Peter Donkor (PLoS ONE)
Amputation in children is rare. However, in recent times, amputation in children has increased and trauma is the leading cause in Ghana. Few studies on the effects of amputation on caregivers particularly of children are available. This study aimed to explore the effects of trauma-related amputations in children on caregivers using qualitative descriptive phenomenological approach. In-depth interviews were conducted with semi-structured interview guide. Ten (10) informal caregivers were purposively selected from the trauma registry of a tertiary facility in Ghana. Data were analyzed manually using the thematic approach described by Collaizi. The findings revealed that trauma-related amputations in children affect the work-role, social life, finances and mental health of the caregivers. Provision of counselling services to address the mental health needs of caregivers and decentralization of orthopaedic and rehabilitation services would lessen the burden of caregiving.